Exploring the differences in the airport competitiveness formation mechanism: evidence from 45 Chinese airports during 2010–2014. Issue 3 (3rd July 2017) - Cui, Qiang; Wei, Yi-Ming; Li, Ye; Li, Wei-xia
ABSTRACT: In this paper, the formation mechanism difference for airport groups is explored. The 45 Chinese airports operating from 2010 to 2014 are classified into 3 groups by a K-means clustering algorithm. Then, the formation mechanism index system is built using seven aspects: Regional Development, Infrastructure Conditions, Operational Strength, Demand Conditions, Support Industry, Service Strength and Technology Index. The formation mechanisms of the 3 airport groups are tested based on 11 basic hypotheses. The results show that different airport groups have different competitiveness formation mechanisms. The conclusions can provide targeted competitiveness cultivation guidance for decision makers at different airports.